Pengaruh Implementasi Sistem Pengendalian Intern Pemerintah (SPIP) Terhadap Pengamanan Aset Tetap di Pemerintah Kota Tasikmalaya - Dewi Apipah, Wulan; Dwi Kusumastuti, Endah; albert, albert (Indonesian Accounting Research Journal, 2023)
Fixed assets play an important role in supporting government activities so they need to be managed properly. Based on LHP BPK 2021, the Tasikmalaya City Government still has problems managing its assets because their fixed asset safeguarding is considered inadequate. SPIP is required to guarantee the implementation of fixed assets safeguarding. The objective of this study is investigate the impact of implementing SPIP elements on Fixed Asset safeguarding in Tasikmalaya City partially and simultaneously. This study employs a quantitative methodology using survey methods. In this study, the population and sample were 36 local government agencies with questionnaires distributed to 72 respondents. The SPSS 26 version was utilized for data analysis, which included multiple linear regression. The results of the study revealed that the SPIP elements had a 59.4% positive and significant effect on the security of Fixed Assets, with only Information and Communication, and Monitoring having a positive and significant effect, while the Control Environment, Risk Assessment, and Control Activities had no effect.